PERHITUNGAN DIMENSI SEAWALL MENGGUNAKAN LAZARUS - Fera Lestari; Randy Setiawan; Dian Pratiwi (Jurnal Teknik Sipil, 2018)
PT.  Daya  Radar  Utama  has  built  and  repaired various  types  of  ships  including  steel,  aluminum alloy, and fiberglass reinforced plastic.  In  general,  Graving  Dock  and  Noahtu  Port Bandar Lampung provide supporting facilities for repairs  of  large  capacity  ships  (maximum  30000 DWT),  Complete  facilities  and  infrastructure  for progress in the field of sea transportation. A wave barrier  is  needed  to  support  the  activities  in Graving  Dock  and  the  Port  of  Noahtu  Bandar Lampung in the form of seawall. Seawall or beach walls  are  beach  buildings  that  are  built  on  the coastline  or  on  land  that  are  used  to  protect  the beach directly from wave attacks. The  location  of  this  study  was  carried  out  in  the city  of  Bandar  Lampung  with  research  objects, namely  on  the  pier  and  PT.  Daya  Radar  Utama. Data  collection  in  this  study  consisted  of  wind data, wave data, tide data, soil data, and sediment data.  These  data  are  obtained  from  the  planning data of the dock construction in the company PT. Daya Radar Utama.To  make  it  easier  to  get  the  dimensions  of  the seawall,  a  tool  is  needed  to  simplify  the calculation.  One  program  that  can  be  used  to simplify  calculating  the  dimensions  needed  in  a seawall plan is Lazarus because it is open source and discusses relatively easy programming.Calculation  of  seawall  dimensions  with  this program  can  be  done  easily  and  quickly, compared  to  manual  calculations.    In  the planning of making seawall stone types affect the seawall.  In making seawall using the program, it is  necessary  to  pay  attention  to  rounding  for  the weight of protected layers.